TECHNETIUM-99M TRODAT-1 NEUROMOLECULAR IMAGING FOR PARKINSONIAN SYNDROME: FIRST EXPERIENCE IN INDONESIAN PUBLIC HOSPITAL - Aliwarga, Randy; Kusumahstuti, Kharisma Perdani; Nugrahadi, Trias; Kartamihardja, Achmad Hussein Sundawa (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2026)
Background: Parkinsonian syndromes are characterized by progressive motor impairment resulting from nigrostriatal dopaminergic degeneration. Although diagnosis is primarily clinical, early disease stages often overlap with non-parkinsonian disorders, leading to misclassification. Dopamine transporter (DaT) imaging provides an objective biomarker for confirming presynaptic dopaminergic loss. However, the only internationally approved tracer, Iodine-123 ioflupane (DaTscan™), remains unavailable in Indonesia due to the absence of high-power cyclotron facilities and logistical constraints. Technetium-99m TRODAT-1, a generator-based alternative, offers a practical solution for countries with limited nuclear infrastructure. Objective: Two patients with confirmed Parkinson’s disease (A, B) underwent brain SPECT/CT imaging using 99mTc-TRODAT-1. Radiotracer preparation followed standard reconstitution and autoclaving procedures, achieving >95% radiochemical purity. Images acquired four hours post-injection were evaluated visually using the Fabiani scale to assess DaT binding patterns. Results: Patient A demonstrated asymmetric uptake loss in the posterior putamen consistent with mid-stage PD, while Patient B exhibited near-complete absence of striatal binding with increased extra-striatal activity, typical of advanced PD with cognitive decline. Both cases confirm that TRODAT-1 provides reliable visualization of nigrostriatal degeneration and remains technically feasible for local production and distribution. Conclusion: 99mTc-TRODAT-1 represents a viable and diagnostically robust DaT imaging option for Indonesia, offering both clinical accuracy and logistical practicality. Broader implementation could substantially improve diagnostic precision and disease staging in parkinsonian syndromes nationwide.